Electrical conductivity of iron-bearing silicate glasses and melts. Implications for the mechanisms of iron redox reactions. (15th September 2015) - Malki, M.; Magnien, V.; Pinet, O.; Richet, P.
Abstract: The electrical conductivity of a series of glasses and melts of the system SiO2 –CaO–MgO–M2 O–"FeO" (M = Li and Na) and of a borosilicate has been measured from room temperature to about 1820 K. For samples with predominantly reduced iron, the conductivity increases markedly upon addition of Na + and still more of Li +, which is consistent with the increasing order Mg 2+, Na +, Li + order of cation mobility. For the oxidized samples the conductivity is in contrast almost not affected by the presence of alkali cations, which agrees with the low mobility of alkali cations that are then serving as charge compensators of tetrahedrally coordinated Al 3+ . The conductivity is higher for oxidized than for reduced samples. As indicated by polarization electrode phenomena and complementary continuous current measurements, this difference is due to an important contribution of electronic conduction caused by electronic charge transfer between iron species that exists in the oxidized samples. The diffusivities of oxygen and divalent cations were then determined from Eyring relationship and the measured conductivities, respectively and compared with the redox diffusivies determined for the same samples. The good agreement found between both kinds of data confirms the controlling role of divalent cations and of oxygen species in the redox kinetics near the glass transition and at high temperatures, respectively. In addition it illustrates that describing melt properties in an integrated manner is becoming possible.